Study of suitable media for laccase synthesis of basidiomycete fungi from Bidoup - Nuiba park and its reactive dye decolorization ability - Hiền, Trần Thị Thu; Hiền, Lê Thị; Huynh, Nguyễn Văn; Hằng, Đinh Thị Thu; Hà, Đặng Thị Cẩm (Vietnam Journal of Biotechnology, 2016)
A fungal strain FBD154 with high laccase production was isolated from Bidoup-Nui Ba Parks, Lam Đong, Vietnam. FBD154 was identified as Polyporus sp. FBD154 based on traditional method and ITS sequence analysis. Polyporus sp. FBD154 synthesized laccase with high activity 74925 U/l on modified TSH1 (200 g/l containing potato extract, 1 g/l casein, 1 g/l rice bran, 5 g/l soybean meal, 10 g/l manose, 3 g/l NH4Cl, 0.3 mM CuSO4, pH 4). Crude laccase of Polyporus sp. FBD154 was applied to decolor several synthetic and commercial dyes. After 30 min, laccase from Polyporus sp. FBD154 could decolorize synthetic dyes at 100 mg/l concentration with efficiency of 60% acid red (NY1), 18% acid red 299 (NY7), 52% acid blue 281 (NY5) and 83% Remazol Brilliant Blue R (RBBR) without mediator. For commercial dyes at concentration of 100 mg/l, color removal efficiency reached to 62% megafix black CLS (CLS) and 72% everzol red LF2B (LF-2B) without mediator. Efficiency of synthetic dye removal by Polyporus sp. FBD154 crude laccase with 200 µM mediator obtained 90% RBBR with violuric acid (VIO) after 30 min; 80% NY5 with hydroxybenzotriazole (HBT) for 24 hours; 87% NY1 with acetosyringone (Ace) for 5 min; 92% NY7, 91% LF-2Band 73% CLS with syringaldehyde (Syr) for 5 min. The obtained evidences show that laccase was synthesized by Polyporus sp. FBD154 with high potential for application in wastewater treatment of textile plants in particular as well a sin detoxification of polycyclic aromatic compounds in general.